2018
DOI: 10.1038/s41598-018-34414-7
|View full text |Cite
|
Sign up to set email alerts
|

Corticohippocampal Dysfunction In The OBiden Mouse Model Of Primary Oligodendrogliopathy

Abstract: Despite concerted efforts over decades, the etiology of multiple sclerosis (MS) remains unclear. Autoimmunity, environmental-challenges, molecular mimicry and viral hypotheses have proven equivocal because early-stage disease is typically presymptomatic. Indeed, most animal models of MS also lack defined etiologies. We have developed a novel adult-onset oligodendrogliopathy using a delineated metabolic stress etiology in myelinating cells, and our central question is, “how much of the pathobiology of MS can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…Importantly, unlike Aze, cuprizone, and other myelinotoxins are not consumed by humans; they do not as closely mimic MS NAWM; and they are not directly implicated in MS pathogenesis. There are also features of OL stress in the genetically engineered OBiden mouse model ( 75 ), but Aze-induced oligodendrogliopathy is acquired and is mechanistically distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, unlike Aze, cuprizone, and other myelinotoxins are not consumed by humans; they do not as closely mimic MS NAWM; and they are not directly implicated in MS pathogenesis. There are also features of OL stress in the genetically engineered OBiden mouse model ( 75 ), but Aze-induced oligodendrogliopathy is acquired and is mechanistically distinct.…”
Section: Discussionmentioning
confidence: 99%
“…At the single-cell level, AIS shortening reduces neuronal excitability according to in silico (Baalman et al, 2013;Vascak et al, 2017;Goethals and Brette, 2020), in vitro (Evans et al, 2015), and in vivo (Jamann et al, 2021) reports. However, other studies show that AIS shortening does not reduce excitability when associated with changes in Nav phosphorylation (Evans et al, 2015), loss of Kv1 channels (Sanders et al, 2020), or alteration of action potential backpropagation (Radecki et al, 2018). At the network level, one study reported AIS shortening and reduced MEA spiking, but the cultures consisted of only excitatory neurons (Sohn et al, 2019).…”
Section: Ais Shortening May Contribute To Cognitive Impairment and Neuronal Network Dysfunctionmentioning
confidence: 99%
“…Alteration of AIS constituents, such as mutations in ion channels or loss of protein complexes, is emerging as a key pathophysiology in a wide variety of neurological conditions in humans (reviewed in (Buffington and Rasband, 2011;Huang and Rasband, 2018)). In the brains of animals, subtle changes in AIS geometry (i.e., length or position along the axon) are reported in models of type 2 diabetes (Yermakov et al, 2018), Alzheimer's disease (Marin et al, 2016), aging (Atapour and Rosa, 2017;Ding et al, 2018), stroke (Hinman et al, 2013), multiple sclerosis-related demyelination (Hamada and Kole, 2015;Radecki et al, 2018), and neuropathic pain (Shiers et al, 2018). This suggests altered AIS geometry could be a common mechanism of CNS dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the AIS was shorter at 24 h when single-cell excitability parameters and network activity recovered to baseline levels. These surprising findings might be explained by studies showing that AIS shortening does not reduce excitability when associated with changes in Nav phosphorylation (Evans et al, 2015), loss of Kv1 channels (Sanders et al, 2020), or alteration of action potential backpropagation (Radecki et al, 2018). Determining how simultaneous AIS shortening in multiple cell types and recovery of neuronal function are related will be critical going forward.…”
Section: Are Ais Geometry and Neuronal Function Linked?mentioning
confidence: 99%
“…Alteration of AIS constituents, such as mutations in ion channels or loss of protein complexes, is emerging as a key pathophysiology in a wide variety of neurological conditions in humans (reviewed in (Buffington and Rasband, 2011;Huang and Rasband, 2018)). In the brains of animals, subtle changes in AIS geometry (i.e., length or location along the axon) are reported in models of type 2 diabetes (Yermakov et al, 2018), Alzheimer's disease (Marin et al, 2016), aging (Atapour and Rosa, 2017;Ding et al, 2018), stroke (Hinman et al, 2013), multiple sclerosis-related demyelination (Hamada and Kole, 2015;Radecki et al, 2018), and neuropathic pain (Shiers et al, 2018). This suggests altered AIS geometry could be a shared mechanism of CNS dysfunction.…”
Section: Introductionmentioning
confidence: 99%